2019
DOI: 10.1111/jpg.12733
|View full text |Cite
|
Sign up to set email alerts
|

Sedimentology, Geochemistry and Reservoir Potential of Sandstones in the Silurian Akkas Formation, Western Iraq

Abstract: The source rock potential of "hot shales" in the Silurian Akkas Formation in Iraq has been investigated by numerous studies, but the reservoir potential of sandstone intervals in the formation has received less attention. This study investigates the sedimentology and geochemistry of sandstones from the Akkas Formation in the Akkas-1, Akkas-3 and KH5/6 wells in western Iraq. The composition of sandstone samples from the Akkas wells is similar; in general they are classified as sub-litharenites, quartz-arenites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Concerning source rock potential of the Paleozoic source rocks in Iraq, Aqrawi et al (2010) [26] revealed that the lower Ordovician shales (assigned to Member 7 of the Khabour Formation, according to Al-Hadidy, 2007, [18]) and the lower Silurian ("hot" shale of the Akkas Formation) could be regarded as principal hydrocarbon source rocks in the Paleozoic sequence of western Iraq, similar to their role across the region in Jordan Syria, Libya, and Saudi Arabia [27,23,25]. The lower "hot" shale unit of the Silurian Akkas Formation, western Iraq, has an average-good source rocks (TOC 1.2-5.25 wt%, mean 2.2 wt%; S2 1.2-8.7 kg/tonne, mean 4.2 kg/tonne) [28]. Whereas, TOC values are 0.17-1.42wt% for the 2750-3000m interval and 0.5-1wt% for the 3570-3650m interval in the Khabour Shale of Akkas-1 well, as suggested by Al-Ameri (2010) [23].…”
Section: Introductionmentioning
confidence: 78%
“…Concerning source rock potential of the Paleozoic source rocks in Iraq, Aqrawi et al (2010) [26] revealed that the lower Ordovician shales (assigned to Member 7 of the Khabour Formation, according to Al-Hadidy, 2007, [18]) and the lower Silurian ("hot" shale of the Akkas Formation) could be regarded as principal hydrocarbon source rocks in the Paleozoic sequence of western Iraq, similar to their role across the region in Jordan Syria, Libya, and Saudi Arabia [27,23,25]. The lower "hot" shale unit of the Silurian Akkas Formation, western Iraq, has an average-good source rocks (TOC 1.2-5.25 wt%, mean 2.2 wt%; S2 1.2-8.7 kg/tonne, mean 4.2 kg/tonne) [28]. Whereas, TOC values are 0.17-1.42wt% for the 2750-3000m interval and 0.5-1wt% for the 3570-3650m interval in the Khabour Shale of Akkas-1 well, as suggested by Al-Ameri (2010) [23].…”
Section: Introductionmentioning
confidence: 78%
“…upper shale) of later Llandovery age (see Aqrawi et al, 2010 for its definition in Iraq). In terms of Iraqi stratigraphy, this entire interval falls within the Akkas Formation of the Western Desert area, in which there is basal hot shale, Hoseiba Member and uppermost Qaim Member (Al-Hadidy, 2007 andAl-Juboury et al, 2019).…”
Section: Megasequence Ap3mentioning
confidence: 98%
“…In the Akkas-1 well, light oil (42° API) was discovered in fractured sandstones and siltstones of the Qaim member, which has been assumed to be sourced from the hot shale of the underlying Hoseiba Member (Al-Habba et al 1994 andAl-Juboury et al 2019). Al-Khafaji et al (2015) concluded that only the Khabour Formation can be regarded as source for the gas and condensate in the Akkas field, whereas the hot shales of the Akkas Formation have not reached a sufficient maturation level in the well investigated.…”
Section: Proven and Potential Reservoirs Of Sequence: S1-ap3mentioning
confidence: 99%
See 2 more Smart Citations